Endothelin-1 gene polymorphisms in patients with peripheral artery disease - Es, Mehmet Ugur; Senol, Sefa; Yuksel, Ahmet; Kargun, Kursat (A. CARBONE Editore, 2016)
Introduction: We purposed to investigate the effects of Endothelin-1 gene polymorphisms (Lys198Asn and rs10478694) that are supposed to play role in atherothrombotic process in patients with peripheral artery disease (PAD). Materials and methods: This prospective study was performed on 320 participants between January 2013 and July 2014. Participants were divided into two groups: Group 1 (PAD group) included 160 patients with PAD (mean age: 54±14 years, 116 males), and Group 2 (control group) included 160 participants (mean age:51±11 years, 112 males) with normal physical examination and duplex ultrasonography findings for PAD. Groups were compared with each other according to clinical and demographic characteristics, levels of some biochemical parameters, and particularly Endothelin-1 gene polymorphisms were determined by real time polymerase chain reaction. Results: The incidences of hypertension, diabetes mellitus, smoking, family history of cardiovascular diseases and fasting glucose levels were significantly higher in PAD group. Both groups were statistically similar according to levels of total, low-density lipoprotein (LDL) and high-density lipoprotein (HDL) cholesterol, triglyceride, urea and creatinine. Comparison of groups according to Endothelin-1 gene polymorphisms and allele frequencies did not yield any statistically significant differences. Conclusion: We found that Endothelin-1 gene polymorphisms were not associated with PAD. Further studies on different polymorphisms of Endothelin-1 may be beneficial.
Keywords: Endothelin-1; Gene polymorphism; Peripheral artery disease